Aplicación de ensayos en discontinuo para la determinación de flujos de metano y dióxido de carbono en la degradación del material vegetal en el embalse Topocoro (2016)
The contribution of tropical reservoirs to emissions of greenhouse gases (GHGs) has been studied recently due to degradation processes and transformation of plant material are carried out in these, which release methane (CH4) and dioxide carbon (CO2), contributing to climate change. In this paper, tests were carried out in batch using plant material from the flood zone of Topocoro (Santander-Colombia) reservoir, in order to determine the flow of CH4 and CO2 of such material, simulating conditions of aerobic flood and previous anaerobic filling. Measurements were performed using gas chromatography-mass gas (GC-MS). The emission rates under anaerobic conditions varied between 118,513 – 377,666 Kg CH4/t.year y 120,870 – 553,758 Kg CO2/t.year, while under aerobic conditions the emission rates were less, with results that varied between 0,73 y 8,83 Kg CO2/t.year . The emissions produced were determinate mainly by the amount of flooded plant material and for the presence of aerobic and anaerobic organisms.